1996
DOI: 10.1901/jaba.1996.29-549
|View full text |Cite
|
Sign up to set email alerts
|

Compliant in a Moment: A Commentary on Nevin

Abstract: Nevin's scholarly and timely discussion attempts to maintain the precarious union of the experimentally derived theory of behavioral momentum with applications of the behavioral momentum construct to human subjects in applied settings. Nevin's discussion adds much‐needed clarification to a process that at times has proven to be awkward for applied researchers. In this commentary, we will address three general questions: (a) Can the applications of behavioral momentum be derived from the theory as conceptualize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 21 publications
2
11
0
Order By: Relevance
“…Similar observations have been made by Smith and Iwata (1997) and Houlihan and Brandon (1996). It should be noted that these (and the current) accounts of the role that may be played by EOs in high-p/low-p procedures rely heavily on inference from observed changes in the probability of compliance to high-p and low-p commands.…”
Section: Analyzing Existing Treatments From An Eo Perspectivesupporting
confidence: 75%
“…Similar observations have been made by Smith and Iwata (1997) and Houlihan and Brandon (1996). It should be noted that these (and the current) accounts of the role that may be played by EOs in high-p/low-p procedures rely heavily on inference from observed changes in the probability of compliance to high-p and low-p commands.…”
Section: Analyzing Existing Treatments From An Eo Perspectivesupporting
confidence: 75%
“…The results of a series of studies have shown that compliance to low-p requests was enhanced when those requests were preceded by the completion of several brief, highly preferred requests/activities (Davis & Reichle, 1996;Horner, Day, Sprague, O'Brian, & Heathfield, 1991;Mace et al, 1988). Although the mechanism responsible for the effects of high-p sequences is the subject of debate (see Brandon & Houlihan, 1997;Houlihan & Brandon, 1996;Nevin, 1996, for discussion), research indicates that the intervention is effective at increasing compliance across a variety of settings and behaviors.…”
mentioning
confidence: 99%
“…Sessions with the second trainer, however, were conducted on an infrequent basis. As the trainer presenting requests becomes established as a source of reinforcement, it may be necessary to apply the high-p request sequence more consistently and frequently for low-p requests delivered by additional trainers to acquire stimulus control over the subjects' compliant responding (Houlihan & Brandon, 1996).…”
Section: Discussionmentioning
confidence: 99%